Public Private Partnership in livestock sector of Bangladesh - Husain, SS; Amin, MR (Bangladesh Journal of Animal Science, 2018)
In Bangladesh the concept of Public Private Partnership (PPP) has been launched very recently. In view of the present need of the country, the Government of Bangladesh issued the Policy and Strategy for Public Private Partnership (PPP) in August 2010, to facilitate the development of core sector public infrastructure and services vital for the people of Bangladesh (Bangladesh Gazette, additional 2010). The PPP program is part of the Government's Vision 2021 goal to ensure a more rapid, inclusive growth trajectory, and to better meet the need for enhanced, high quality public services in a fiscally sustainable manner. It is very practical to understand that only public or private sector along could not able to cope with all the essential needs of the country. It is also eventually true that there are almost equally distributed trained personnel in both the field having variable opportunities. Government resources are not enough always to run huge development of the country. On the other hand it is not always possible for the private sector to start with the view to build up all the facilities alone to meet up the demand of the nation. Thus PPP has been termed as effective vehicle for the integrated development of the country. Bang. J. Anim. Sci. 2017. 46 (3): 172-178